3D printing of kaolinite clay with small additions of lime, fly ash and talc ceramic powders (2019)
Direct ink writing technique, an extrusion based additive manufacturing process, has been used to fabricate kaolinite clay based-ceramics with several inexpensive ceramic powders: lime, fly ash and talc. All the above materials are commonly used in the traditional ceramics industry, in both small and large industries, and therefore available worldwide. This research shows the simplicity of the process feasible not only for companies but also for individual users. The samples were fabricated with water to clay ratios (W/C) between 0.68 and 0.72. Additives were tested in 3.0, 5.0 and 7.0 wt.% with respect to the clay contents, although 3 wt.% of additives worked best. Cylindrical samples were fabricated with 20 mm in diameter and 20 mm in height in order to test their compressive strength and density. Measurement samples were previously cured for three days at room temperature and then exposed to 1100 °C for 1 h. The powdered additives and their corresponding mixtures with clay were characterized with scanning electron microscopy, X-ray fluorescence and X-ray diffraction techniques. Results showed that samples with 0.70 W/C ratio and using fly ash as an additive were the best in terms of workability, mechanical properties and surface finishing.